Fathers' perceptions of caregiving in childhood and current mentalizing with their preschool children. Issue 3 (2nd July 2016) - Tharner, Anne; Altman, Frida Henriques; Væver, Mette
Abstract: We examined fathers' capabilities to reflect on their children's mental states (mind-mindedness) and their use of mental state language when interacting with their preschool child and how this related to fathers' perceptions of caregiving in their childhood. Participants were 39 European (UK and Danish) fathers and their 3–5 year-old children. We assessed paternal mind-mindedness (offline) based on mentalistic descriptions of the child, and fathers' use of mental state language (online) with a shared picture book task. The Danish Father Attachment Interview was used to assess fathers' childhood caregiving perceptions of both their mother and their father. Length of paternity leave (LPL) was included as an indirect measure of paternal involvement. We found that greater paternal mind-mindedness was related to higher use of mental state language in the picture book task. Also, fathers' positive model of caregiving of their mother (MCM) and LPL were related to paternal mind-mindedness: fathers with an MCM characterized by closeness, compassion and understanding were more mind-minded than fathers who lacked such a positive caregiving model. Longer paternity leave as an index of paternal involvement was related to greater mind-mindedness. Trimmed path models from multiple regression analyses showed that fathers' positive MCM and LPL were directly related to mind-mindedness. There was also an indirect pathway from fathers' positive MCM through mind-mindedness to the use of mental state language. Findings suggest that both past caregiving experiences and fathers' involvement with the child play a role in fathers mentalizing capabilities and behaviour when interacting with their child.